(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2020)
Background: In 2019 Bangladesh faced largest outbreak of Dengue fever (DF) and clinicians observed some changing patterns in presentation and laboratory findings of DF. This study intends to find the changing patterns of dengue and its different manifestations including unusual one. Material and Method: This study deals around 220 dengue patient visited to popular Medical College Hospital as inpatient of medicine department during the period 1st July 2019 to 31st December 2019. Chi-square statistics was used find the intra and inter association among the disease mainfestatons and multinominal logistic regression analysis was used to compare disease severity. Results: Among 220 dengue serologically positive cases, the most common age group affected was 18-49 years (68.6%). Regarding the known common features like fever (91.8%), vomiting (50.2%), headache (48.2%), were frequent among the patients but myalgia (19.6%), rash (14.5%), retro orbital pain (14.1%) were not so common. Presence of unusual features like abdominal pain (49.3%), loose motion (55%) and cough/ breathlessness (41.4%) ascites (53.2%), pleural effusion (51.8%), hepatomegaly (32.3%), peri-gallbladder edema (35.5%) and splenomegaly (15.1%) were also common among dengue patients. Serum Lipase was also increased in (28.8%) cases suggesting pancreatitis. Conclusion: Unusual Manifestations of dengue fever is common. As the spread of dengue is increasing with significant morbidity and mortality, it is extremely important for the clinicians to know about its unusual manifestations. J Bangladesh Coll Phys Surg 2021; 39(1): 9-18